Lifelong Learning as Form of Human Resources Development - Hečko , Štefan; Řihák, Radim; Malátek, Vojtěch (Edukacja Ekonomistów i Menedżerów, 2014)
The article deals with the issue of lifelong education from the view point of the develop‑ ment of the personality of an individual. Nowadays development of national economies is not possible without continuous increasing of the level of education of workers – human resources. Lifelong education thus inevitably interferes into the life of every individual, regardless of their age, sex or job position. These are fundamental starting points from which the article comes out. The objective of the paper is to show that in present days lifelong education has a non‑substitutable place in the development of human resources. The partial objective is to analyze the concept of lifelong learning from the concept point of view both theoretically and on the basis of the secondary analysis of the representative research according to the results publicized by the Czech Statistical Office and to empha‑ size the importance of formal, non‑formal and informal education in the development of human resources and employment. The set goal is achieved by means of clarifying the EDUCATION OF ECONOMISTS AND MANAGERS No. 3 (33) 2014_Rihak_Malatek_Hecko 36 Radim Řihák, Vojtěch Malátek, Štefan Hečko term lifelong education, understood as interconnection of the possibility of educating in formal (school) and non‑formal (out‑of school) sector in one unit, concurrently there are used national (Czech) and international documents, dealing with lifelong learning and passages between education and employment. The necessity of the conceptual intercon‑ nection of the educational system is the prerequisite for enabling acquiring qualifications in various ways, and that is in the course of the whole life of an individual. In the first part the article than deals with theoretical basis of lifelong education, which it comes out from the analysis of documents of significant European and world institutions, as from the Memorandum of the EU on lifelong learning, from documents of the OECD, from the concept of permanent education of the Council of Europe or from the conceptual document Learning to be issued by the organization of the UNESCO. Through analysis of the documents and further literary sources the authors embark on the description of the contemporary concept of lifelong education which has been applied since the 1990s century. The fundamental issue of professional education and preparation to usability in the job life is in this concept. The second part of the article analyses statistical data related to single forms of lifelong education – formal education, non‑formal education and informal education from the point of view of the human resources development. The article presents concrete data on involvement of employees and employers into the process of lifelong learning, whereas its conclusion summarizes the solved issue and reaches the number of interesting pieces of knowledge.